PENGEMBANGAN INDUSTRI CRUDE PALM OIL BERKELANJUTAN DENGAN MENGGUNAKAN MODEL GEO-SPATIAL MULTICRITERIA DECISION ANALYSIS - Gunarta, I Ketut (Bumi Lestari; Vol 13 No 1 (2013), 2013)
Abstract Development of crude palm oil industry in Indonesia and Malaysia have been able to change the map of world vegetable oil in a short time. In 1985, Indonesia palm oil production reached 1.3 million tons. However, in 2007 Indonesia has surpassed the total production of CPO Malaysia. Indonesia’s CPO total production in 2011is 23 million tons. To produce that amount of production volume, there are at least 4 million ha of land to produce raw material for the factory. With the next target of 50 million tons of production will of course be a lot of land to be prepared or converted. However, the increasing of CPO production is not always have a positive impact. Forest damage caused by the opening of oil palm plantation and is still a lack of consideration to increase CPO production through increased productivity of the land received many responses from various parties environmentalists. Approximately 400,000 ha of forests in Indonesia per year be converted into oil palm plantations. The use of forest land for oil palm plantations is one of the growing threat of Indonesia’s CPO production so necessary to control the development of this industry.This paper provides an alternative optimal solution to the development of palm oil industry by building a decision support system that integrates GIS with spatial analysis models esspecially multicriteria decision making. This spatial based decision support system has a capability to accommodate the limitations of land development, environmental constraints, transportation facilities and transportation networks as well to get the optimal CPO industry development decision.
Keywords: Keywords: industry developmen, GIS, crude palm oil, spatial analysis model